2021
DOI: 10.3390/cancers13040856
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenetic Features and Current Management of Glioblastoma

Abstract: Glioblastoma (GBM) is the most common form of primary malignant brain tumor with a devastatingly poor prognosis. The disease does not discriminate, affecting adults and children of both sexes, and has an average overall survival of 12–15 months, despite advances in diagnosis and rigorous treatment with chemotherapy, radiation therapy, and surgical resection. In addition, most survivors will eventually experience tumor recurrence that only imparts survival of a few months. GBM is highly heterogenous, invasive, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 322 publications
(353 reference statements)
0
33
0
6
Order By: Relevance
“…A subsequent study done by Brennan et al [ 6 ] identified other significantly mutated genes in GB: IDH1, PDGFRA, leucine-zipper-like transcriptional regulator 1 (LZTR1), spectrin alpha 1 (SPTA1), ATRX, gamma-aminobutyric acid type A receptor subunit alpha 6 (GABRA6) and KEL, as well as amplifications in chromosome 4 (PDGFRA), chromosome 7 (EGFR, MET, CDK6) and chromosome 12 (CDK4, MDM2). Additionally, a TCGA-based study showed that GB tumors often exhibit alterations of the TP53, RB and RTK/Ras/PI3K signaling pathways [ 6 ], contributing to cancer cell migration, invasion, proliferation, differentiation and survival [ 105 ].…”
Section: Pathogenesis Of Glioblastomamentioning
confidence: 99%
“…A subsequent study done by Brennan et al [ 6 ] identified other significantly mutated genes in GB: IDH1, PDGFRA, leucine-zipper-like transcriptional regulator 1 (LZTR1), spectrin alpha 1 (SPTA1), ATRX, gamma-aminobutyric acid type A receptor subunit alpha 6 (GABRA6) and KEL, as well as amplifications in chromosome 4 (PDGFRA), chromosome 7 (EGFR, MET, CDK6) and chromosome 12 (CDK4, MDM2). Additionally, a TCGA-based study showed that GB tumors often exhibit alterations of the TP53, RB and RTK/Ras/PI3K signaling pathways [ 6 ], contributing to cancer cell migration, invasion, proliferation, differentiation and survival [ 105 ].…”
Section: Pathogenesis Of Glioblastomamentioning
confidence: 99%
“…The current oncological treatment of glioblastoma patients has been excellently reviewed elsewhere [ 129 ]. Although temozolomide might exert some anticonvulsant effects [ 130 ], here we will focus on pharmacological means of addressing glioma-associated seizures since there is an increasing understanding of the shared mechanisms of tumor progression and epileptogenicity, suggesting that certain compounds could establish novel strategies for the treatment of glioblastoma patients presenting epileptic seizures.…”
Section: Glutamatergic Mechanisms Of Glioma Progression and Tumor-associated Epilepsymentioning
confidence: 99%
“…For a full dataset, it is sufficient to label the 10% of the available slices, the full-volume segmentation will be done by interpolation. After the tumor is correctly identified (6), binary images are produced (7) and the tumor volume can be quantified by the Analyze Particles Fiji plugin (8). This volume can also be rendered in 3D via the software VGStudio MAX 4.3 together with the original brain dataset (9).…”
Section: Supplementary Materialsmentioning
confidence: 99%
“…It has a poor prognosis with a survival ranging from 7 months [ 3 ] to 12–15 months [ 4 , 5 ] with a long-term survival probability less than 3% [ 6 ]. GBM treatment involves surgery, chemotherapy, and radiation therapy (RT); due to the radio- and chemo-resistance and highly infiltrative growth of GBM, present treatments are only able to slow down the development of the disease permitting an increase of the survival by a few months [ 7 ]. For all these reasons, there is the need for an effective therapy for the management of gliomas.…”
Section: Introductionmentioning
confidence: 99%